First-Line Treatment Options for PD-L1–Negative Non-Small Cell Lung Cancer: A Bayesian Network Meta-Analysis - Peng, Ling; Liang, Wen-Hua; Mu, De-Guang; Xu, Song; Hong, Shao-Dong; Stebbing, Justin; Liang, Fei; Xia, Yang (Frontiers in Oncology, 2021)
Background: First-line treatment strategies for PD-L1 (programmed death-ligand 1) negative non-small cell lung cancer (NSCLC) patients include chemotherapy and combinations with anti-angiogenesis drugs and/or immune checkpoint inhibitor. We conducted a Bayesian network meta-analysis to evaluate the efficacy of these therapeutic options. Methods: We included phase III randomized controlled trials comparing 2 or more treatments in the first line setting for NSCLC including data in PD-L1 negative patients. First-line strategies were compared and ranked based on the effectiveness in terms of overall survival (OS) and progression-free survival (PFS). A rank was assigned to each treatment after Markov Chain Monte Carlo analyses. Results: Fourteen trials involving 14 regimens matched our eligibility criteria. For OS, none of the treatment were significantly more effective than chemotherapy. Nivolumab plus ipilimumab plus chemotherapy was probably the best option based on analysis of the treatment ranking (probability = 30.1%). For PFS, nivolumab plus chemotherapy plus bevacizumab, atezolizumab plus chemotherapy plus bevacizumab, and atezolizumab plus chemotherapy were statistically superior to chemotherapy in pairwise comparison. Nivolumab plus chemotherapy plus bevacizumab was likely to be the preferred option based on the analysis of the treatment ranking (probability = 72.9%). Conclusions: Nivolumab plus chemotherapy, in combination with angiogenesis inhibition or anti-CTLA-4 had maximal benefits for NSCLC patient of PD-L1 negative expression. These findings may facilitate individualized treatment strategies. Safety at an individual patient level should be considered in decision-making. Further validation is warranted.